2022
DOI: 10.1002/jctb.7106
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatible enhancement of poly(ethylene terephthalate) (PET) waste films by cold plasma aminolysis

Abstract: BACKGROUND Poly(ethylene terephthalate) (PET) waste films were treated by cold plasma aminolysis to graft primary amino groups (‐NH2) and the surface biocompatibility of the polymer was improved. Aminated PET waste films were obtained by applying radiofrequency (RF) plasma treatment of either diethylenetriamine (DTA) or ethylenediamine (EDA). Aminolysis was applied during 5, 10 and 15 min at plasma power levels of 150, 175 and 200 W. RESULTS Water contact angle study revealed that the surface of PET waste film… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 52 publications
(118 reference statements)
0
10
0
Order By: Relevance
“…Composite polymers tend to be used in cardiovascular applications [ 1 ] due to their versatility in terms of their mechanical, thermal, and physicochemical properties, which are achieved by mixing a disperse phase (filler) and a continuous phase (polymeric matrix) [ 1 , 2 ]. Several investigations with different polymeric matrices have been conducted to obtain new composite materials for cardiovascular implants, especially with alginate, poly(D,L-lactic-co-glycolic acid) (PLGA), polytetrafluoroethylene (PTEF), polyethylene terephthalate (Dacron), and polyurethane (PU) [ 3 , 4 , 5 , 6 , 7 , 8 ]. Between these polymeric matrices, polyurethanes are listed as the first candidate for the production of vascular grafts owing to their better compliance, biocompatibility, mechanical properties, and adaptation to different manufacturing technologies [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Composite polymers tend to be used in cardiovascular applications [ 1 ] due to their versatility in terms of their mechanical, thermal, and physicochemical properties, which are achieved by mixing a disperse phase (filler) and a continuous phase (polymeric matrix) [ 1 , 2 ]. Several investigations with different polymeric matrices have been conducted to obtain new composite materials for cardiovascular implants, especially with alginate, poly(D,L-lactic-co-glycolic acid) (PLGA), polytetrafluoroethylene (PTEF), polyethylene terephthalate (Dacron), and polyurethane (PU) [ 3 , 4 , 5 , 6 , 7 , 8 ]. Between these polymeric matrices, polyurethanes are listed as the first candidate for the production of vascular grafts owing to their better compliance, biocompatibility, mechanical properties, and adaptation to different manufacturing technologies [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cold plasma aminolysis, also results in ultraviolet radiation and free electrons generation to sterilize the waste films. 149 With low-pressure microwave plasma, the use of ammonia and a mixture of nitrogen and hydrogen were compared. It was found that almost 2 -NH 2 /nm 2 can be incorporated into PET films, which was not dependent on the treatment used.…”
Section: Cold Plasma Aminolysismentioning
confidence: 99%
“…The surface aminolysis involves the interaction of hydrolysed or non-hydrolysed PET surfaces with aliphatic amines such as 4-amino-1-butanol, 128 diethylenetriamine (DTA), 101 ethylenediamine (EDA), 99,100,102 triethylenetetramine, 129,130 under catalytic conditions (sodium/zinc acetate or bases) or simple heating (Fig. 4c and Table 1(4)).…”
Section: Overview Of the Functional Upcycling Strategy For Different ...mentioning
confidence: 99%
“…4c and Table 1(4)). Surface aminolysis can be also realized via NH 3 plasma treatment 101 (Table 1(4)). Amino groups formed during aminolysis can serve as active centres for further organic transformations (Fig.…”
Section: Overview Of the Functional Upcycling Strategy For Different ...mentioning
confidence: 99%
See 1 more Smart Citation